PEMBELAJARAN BERBASIS ONLINE SEBAGAI UPAYA STUDY FROM HOME MELALUI PENGGUNAAN SYSTEM AND APPLICATION OPEN KNOWLEDGE PADA MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIKINFORMATIKA DAN KOMPUTER UNIVERSITAS NEGERI MAKASSAR - Ainul Hidayah; Abdul Muis Mappalotteng(; Hendra Jaya (UNM Journal of Technology and Vocational, 2023)
The study aims at analyzing the influence of learning process, the lecturer’s competence, and students’ activities on learning effectiveness. The research population was the students of Informatics and Computer Engineering Education Study Program at the State University of Makassar of batch 2019 and 2020 with 83 samples. The analytical methods used were descriptive analysis, inferential analysis with normality, linearity, multicolinearity, and autocorrelation as well as the hypothesis testing of multiple linear reegression. Data collections were obtained by employing observation, questionnaire, and documentation. Based on the result of hypothesis testing with regression analysis, the first hypothesis of the study surmised that the learning process gives significant influence on the learning effectiveness and it is attested. Then, the second and third hypotheses of the study surmised that the lecturer’s competence and the students’ activities give influence on the learning effectiveness and it is attested.